Stock price movements : does change in energy price matter? - Abdul Jalil, Norasibah; Mat Ghani, Gairuzazmi; Daud, Jarita; Ibrahim, Mansor (Penerbit UPSI, 2009)
This paper investigates the impact of oil price shocks on the Malaysian stock market. The co-integration test results documented zero co-integration equation. This finding implies no long-run relationship between the variables in the system. The causality test which looks at short run dynamic interactions between the variables also documented the same finding where shocks in all types of oil prices do not impose any effect on movements in stock price. This finding leads us to conclude that, a change in oil price(s) has no significant effect on stock market both in the short-run and longrun. These findings also lead us to conclude thaPt, change in oil price, particularly domestic oil price1 cannot be used as a policy tool in adjusting the stock market in any case shocks in oil price strike again in future.